Using the Probability of Cesarean from a Validated Cesarean Prediction Calculator to Predict Labor Length and Morbidity - Hamm, Rebecca F.; Downes, Katheryne L.; Srinivas, Sindhu K.; Levine, Lisa D. (American Journal of Perinatology, 2019)
Objective To determine if increasing predicted risk of cesarean was associated with longer labor length and increased morbidity among women undergoing induction with an unfavorable cervix.Study Design Using a publically available database, we evaluated whether a previously validated prediction model for cesarean delivery after induction was associated with labor length, maternal morbidity (third-/fourth-degree lacerations, endometritis, blood transfusion, wound infection, venous thromboembolism, hysterectomy, intensive care unit admission, and death), and neonatal morbidity (blood transfusion, encephalopathy, intraventricular hemorrhage, severe respiratory distress syndrome, necrotizing enterocolitis, and sepsis). Full-term (≥37 weeks) singleton gestations with intact membranes and an unfavorable cervix (Bishop score ≤6 and dilation ≤2 cm) undergoing induction of labor were included.Results A total of 8,466 women met the inclusion criteria. Each category increase in cesarean probability (<20, 20–39.9, 40–59.9, ≥60%) was associated with an increase in labor length (9.6, 10.8, 11.7, and 11.9 hours, respectively; p < 0.001). With increasing predicted probability of cesarean there, was also a significant increase in maternal morbidity with each category (2.6, 4.7, 5.1, 6.1%; p = 0.001) and increase in neonatal morbidity (0.9, 1.5, 2, 2.2%; p = 0.002).Conclusion Using a validated prediction model for cesarean delivery among women induced with an unfavorable cervix, increasing predicted probability of cesarean is associated with longer labor length and increased maternal and neonatal morbidity.
Keywords: calculator; cesarean section; induction of labor; labor length; maternal morbidity; neonatal morbidity; unfavorable cervix